THE EFFECT OF YOUTH ATTITUDES TOWARD THE BEHAVIOUR PREVENTION OF SEXUALLY TRANSMITTED DISEASES IN THE 3RD GRADE OF THE ISLAMIC SENIOR HIGH SCHOOL (MA) “X”, SUB-DISTRICT OF MRANGGEN, DEMAK REGENCY - Dewi Puspitaningrum; Eka Oktavia Puspitasari; Agustin Rahmawati (Universitas Muhammadiyah Semarang, 2017)
Background: STD (Sexually Transmitted Diseases) is a kind of RTI (Reproductive Tract Infections) transmittedthrough sexual intercourses. Bacteria causing such kind of infections can be fungi, viruses and parasites.Women are more susceptible to suffering reproductive tract infect ions than men because, compared men’s reproductive system, theirs is closer to the anal and urinary systems. According to UNICEF (2012) about 110,000 people aged 10-19 years died of STD and HIV AIDS in 2012. And from the data of KPAN (2011) young age 20-29 years the highest group affected by PMS was 46.4%. In women, RTI is rather difficult to identify because its symptom is less clear than that in men. Among other kinds of RTIs, STD is a kind of infectious diseases frequently found and transmitted via sexual intercourses. STD’s types are syphilis, gonorrhea,limfogranuloma venereal, genital warts, herpes and etcetera. Based on the Health Profile of Central Java Province in 2012, the type of STD that was subject to treatments was one identified according to the syndrome.And, it was cured based on the standard. The number of cases found Central Java Province in 2012 was 8,671,less than those found in 2011 (10,752 cases). Purpose: To find out how the youth attitudes toward the prevent ionof sexually transmitted diseases in the 3rd Grade of the Islamic Senior High School (MA) “X” Sub-district ofMranggen, Demak Regency. Method: This research was a descriptive research that used a cross sectional approach. The number of population was 70 people. The sampling technique used was probability sampling, involving 59 people . Results: From the results of this study indicate the age of students and students on average 16-19 years, most respondents aged that students and girls aged 17 years. The attitude of adolescents about the prevention of sexually transmitted diseases that students and teenagers most of the youth attitudes support against the prevention of sexually transmitted diseases as many as 30 students (50.8%) and unsupportive attitude as many as 29 students (49.2%) .And the positive prevention of adolescents against disease Contagious by 42 students (71,2%) and negative prevention by 17 students (28,8%) The influence of adolescent attitude toward prevention of infectious disease has p-value value equal to 0,015 so there is influence from adolescent attitude toward prevention of infectious disease. Conclusion: From the results of the study showed that some still have a high percentage of respondents who still do not understand about the attitude of prevention of sexuallytransmitted diseases such as having sex with multiple partners and by using condoms during intercourse withmultiple partners Keywords: Attitudes,Prevention of Sexually Transmistted Diseases